Gaya Kepemimpinan Penanggung Jawab Unit Terhadap Response Time Ambulans DKI Jakarta - Alfian, Sukmawansyah; Tri, Kurniati; Giri, Widakdo; Eni, Widiastuti; Suatmaji, Suatmaji (Universitas Malahayati, 2024)
ABSTRACT Healthcare is becoming an increasingly important need for people in today's modern era. The quality and speed of nursing services provided is crucial, such as ambulance calls especially in emergency situations. An effective leadership style that are upheld by the leader (unit person in charge) can motivate and guide nurses to achieve the targets set, as well as improve their performance in providing quality services to patients. The aim of this research is to determine the correlation between the person in charge of the ambulance unit leadership style and the ambulance response time in Pusat Krisis Dan Kegawatdaruratan Kesehatan Daerah Provinsi Dki Jakarta, North Jakarta Region. This research uses quantitative methods with an observational analytical design with a cross-sectional approach. The sample in this study was 76 operational nurses from 11 ambulance units in the North Jakarta area. Based on the age of the ambulance nursing personnel, they are in the age group > 25 years. Based on gender, the majority are male. The response time achievement identification is in the